2019
DOI: 10.1007/s12671-019-01176-w
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Parenting in Secondary Child Mental Health: Key Parenting Predictors of Treatment Effects

Abstract: Emerging evidence supports the positive effects of Mindful Parenting as a clinical intervention in the context of child psychopathology; however, previous studies have not considered the specific parenting predictors of improvements in child outcomes. Methods Parents accessing a child and youth secondary mental health care center participated in an 8-week Mindful Parenting training (n = 89). The effects of the Mindful Parenting training were assessed on parent-reported child's psychopathology, parents' own psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
0
39
2
Order By: Relevance
“…It is therefore surprising that especially these two domains of parental stress did not improve. Earlier studies that examined the effectiveness of mindful parenting group training have found improvements in parenting problems and the parent-child relationship (Bögels et al, 2014; Emerson et al, in press; Potharst et al, in press b). Also, in a study comparing mindful parenting training in clinical versus non-clinical settings, in which the same questionnaire was used as the one in the current study, improvements in problems with parenting and in the parent-child relationship were reported by the parents after the training in both settings (Potharst et al, in press a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore surprising that especially these two domains of parental stress did not improve. Earlier studies that examined the effectiveness of mindful parenting group training have found improvements in parenting problems and the parent-child relationship (Bögels et al, 2014; Emerson et al, in press; Potharst et al, in press b). Also, in a study comparing mindful parenting training in clinical versus non-clinical settings, in which the same questionnaire was used as the one in the current study, improvements in problems with parenting and in the parent-child relationship were reported by the parents after the training in both settings (Potharst et al, in press a).…”
Section: Discussionmentioning
confidence: 99%
“…It can also aid parents in becoming more attentive toward their children, to what they communicate (both in words and by the non-verbal signals provoked), and in terms of emotional availability. Although Mindful Parenting training has mainly been applied to parents of children with psychopathology or developmental problems (Singh et al, 2007; Bögels et al, 2014; Meppelink et al, 2016; Emerson et al, in press), it has also been shown to be effective in reducing parental stress in a preventive setting (Potharst et al, in press a). A study by Potharst et al (in press b) showed that a Mindful Parenting training adjusted for mothers with a toddler, the “Mindful with your toddler” training, was effective in reducing parental stress, as well as in improving mother-child interactions, and child behavior problems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to child age, the nature of the child's difficulties is important when developing mindful parenting programs. To date, mindful parenting interventions have mainly been studied in parents of children with externalizing problems (for example, Haydicky et al, 2015 ) or with a range of mental health diagnoses (Emerson et al, 2019 ). They have not yet been studied in parents of children with only internalizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…They have not yet been studied in parents of children with only internalizing problems. Both parenting stress and over-reactive parenting have been identified as potential mediators of the relationship between mindful parenting and child externalizing problems (Burgdorf et al, 2019 ; Emerson et al, 2019 ). However, little is known about potential mediators between mindful parenting and child internalizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…Given the diverse range of samples included in the Special Issue, Boekhorst et al's work and its implications for such disparities present a promising avenue for future work in this area. Lastly, Emerson et al (2021) explored parenting predictors of improvement following participation in a mindful parenting intervention. In this respect, the authors' work provides important insight into how parent and child factors might interact and influence intervention outcomes.…”
mentioning
confidence: 99%